2023
DOI: 10.1007/s10853-023-08408-4
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional role of carbon dot-based polymer nanocomposites in biomedical applications: a review

Abstract: Carbon-based 0D materials have shown tremendous potential in the development of biomedical applications of the next generation. The astounding results are primarily motivated by their distinctive nanoarchitecture and unique properties. Integrating these properties of 0D carbon nanomaterials into various polymer systems has orchestrated exceptional potential for their use in the development of sustainable and cutting-edge biomedical applications such as biosensors, bioimaging, biomimetic implants and many more.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…The HRTEM images of Ch-OL/CQD@Glu are represented in Figure g (magnified at 20 nm) and Figure h (magnified at 5 nm). It is observed that CQDs are uniformly and densely dispersed in the composite without any agglomeration, which is due to the situation of CQD in the OL-derived Ch network restricting the possibilities of agglomeration . Further, grain sizes are measured from the selected-area electron diffraction (SAED) analysis of the Ch-OL/CQD@Glu nanocomposite and are represented in Figure i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRTEM images of Ch-OL/CQD@Glu are represented in Figure g (magnified at 20 nm) and Figure h (magnified at 5 nm). It is observed that CQDs are uniformly and densely dispersed in the composite without any agglomeration, which is due to the situation of CQD in the OL-derived Ch network restricting the possibilities of agglomeration . Further, grain sizes are measured from the selected-area electron diffraction (SAED) analysis of the Ch-OL/CQD@Glu nanocomposite and are represented in Figure i.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that CQDs are uniformly and densely dispersed in the composite without any agglomeration, which is due to the situation of CQD in the OL-derived Ch network restricting the possibilities of agglomeration. 43 Further, grain sizes are measured from the selected-area electron diffraction (SAED) analysis of the Ch-OL/CQD@Glu nanocomposite and are represented in Figure 2i. Electron microscopic study of the composites with and without glucose gives a distinctive idea regarding the interaction of glucose with the matrix.…”
Section: Electron Microscopic Studymentioning
confidence: 99%
“…In a rough projection, 31.8 g of CDs WL-Oxi is enough to prepare >140,000 cm 2 , or 14 × 1 m for convenience, of a packaging/dressing film that is 0.1 cm thick with a CDs WL-Oxi concentration equivalent to the CDs' MBC (2.25 mg/mL). These results suggest a sufficiently wide window of safe applications of CDs WL-Oxi in areas such as antibacterial wound dressing 47 and food packaging. 48 ■ CONCLUSIONS Fluorescent CDs WL-Red can be synthesized from a mixture of citric acid and cysteine, conveniently but in a low yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One of the most studied systems is those in which two-dimensional allotropes of carbon and their derivatives such as monolayer graphene (G), graphene oxide (GO), reduced graphene oxide (rGO), and functionalized graphene oxide (-f-GO) are employed to unveil their antimicrobial potential. The 2D analogues of G provide an excellent opportunity to revamp their structures and extend the scope of their applications [ 23 26 ]. Several nano-analogues of these materials can be developed by various chemical modification methods (functionalization, doping, stacking, etc.…”
Section: Introductionmentioning
confidence: 99%